Unveiling the Importance and Evolution of Design Components Through the “Tree of Blockchain” - Spychiger, Florian; Tasca, Paolo; Tessone, Claudio J. (Frontiers in Blockchain, 2021)
This study covers the evolutionary development of blockchain technologies over the last 11 years (2009 – 2019) and sheds lights on potential areas of innovation in heretofore unexplored sub-components. For this purpose, we collected and analysed detailed data on 107 different blockchain technologies and studied their component-wise technological evolution. The diversity of their designs was captured by deconstructing the blockchains using the Tasca-Tessone taxonomy to build what we call the "tree of blockchain" composed of blockchain main and sub-components. With the support of information theory and phylogenetics, we found that most design explorations have been conducted within the components in the areas of consensus mechanisms and cryptographic primitives. We also show that some sub-components like Consensus Immutability and Failure Tolerance, Access and Control layer and Access Supply Management have predictive power over other sub-components. We finally found that few dominant design models - the genetic driving clusters of Bitcoin, Ethereum and XRP - influenced the evolutionary paths of most of the succeeding blockchains.